Decomposition of a manganese complex loaded on TiO2 nanoparticles under photochemical reaction - Madadkhani, Sepideh; Nandy, Subhajit; Aleshkevych, Pavlo; Chae, Keun Hwa; Allakhverdiev, Suleyman I.; Najafpour, Mohammad Mahdi (Pergamon Press Ltd., 2024)
Water splitting, through electrochemical and photochemical methods, is a promising approach for large-scale hydrogen production. However, the efficiency of these methods is hindered by the water-oxidation reaction (WOR). A variety of Mn complexes have been explored as potential models for water-oxidizing complex in Photosystem II. Among different Mn complexes, [H2O(terpy)MnIII(mu-O)2MnIV(terpy)H2O](NO3)3 (1, terpy = 2,2':6 ' 2 ''-terpyridine) has been extensively studied under WOR conditions. In this study, the reactivity of 1 is investigated when loaded onto TiO2 nanoparticles and subjected to photochemical conditions. Our main goal was to identify possible products that could arise from the conversion of 1 given the specified conditions. After conducting various analytical methods, it was determined that the reaction yielded MnOx and Mn(II) species as the resulting reaction products. These findings offer valuable insights into the progress of advanced WOR catalysts and the underlying mechanism of efficient water splitting for energy storage.